Increasing exposure to complementary and alternative medicine treatment options through the design of a social media tool. Issue 2 (4th May 2019) - Plachkinova, Miloslava; Kettering, Vanessa; Chatterjee, Samir
ABSTRACT: The current study outlines the creation of an online community designed to connect patients to providers of Complementary and Alternative Medicine (CAM) and western biomedicine. The purpose of the site was to create a forum for patients and healthcare providers to share information and social support regarding eight popular CAM treatments. First, we created a prototype and pilot tested it through a usability analysis. Second, we conducted semi-structured interviews with 12 key stakeholders from the CAM, biomedicine, and patient populations. Third, we conducted a content analysis of the discussion forums to examine common posting behaviour. We found that CAM providers were the most active contributors to the forums. This project provides proof of concept for using an online community platform to connect patients and CAM providers. Future work should attempt to engage Western medicine providers while studying techniques and features that best engage users.